Respiratory physiotherapy in paediatrics - L. M. Davids (AOSIS, 1982)
The approach to respiratory physiotherapy followed at the Red Cross War Memorial Children's Hospital is described. An overview of therapy for the neonate, the child after surgery, the acutely ill child and the child attending the Physiotherapy Department as an outpatient, is given. Stress is laid on treatment of the child and not only his respiratory problem.